Plasticity of Respiratory Function Accommodates High Oxygen Demand in Breeding Sea Cucumbers - Ru, Xiaoshang; Zhang, Libin; Liu, Shilin; Yang, Hongsheng (Frontiers in Physiology, 2020)
Physiological plasticity allows animals to adjust their physiological function to abiotic and biotic variations. It has been mostly studied in the context of response to external factors and not much is known on how animals adjust their physiology to cope with variations in internal conditions. The process of reproduction implies gonadal maturation and other internal changes, bringing various challenges to the animal such as an increased demand for energy and oxygen. Here, the capacity of the sea cucumber, Apostichopus japonicus to adjust its respiratory function and physiological mechanisms during reproduction was studied using a time-lapse videography and metabolomics approach. The results showed that reproduction caused a significant increase in oxygen consumption in A. japonicus. Interestingly, breeding sea cucumbers can accommodate the high oxygen demand by accelerating respiratory rate. However, to maintain a necessary high level of respiratory activity during reproduction, sea cucumbers need consume large amounts of adenosine triphosphate (ATP). In addition, the metabolomic data suggests that oxidative stress and hormone regulation are the physiological mechanisms linking reproduction and respiratory function. Altogether, these findings suggest that plasticity of respiratory function is an effective tactic to cope with high oxygen demand during reproduction.